2001
DOI: 10.1074/jbc.m001550200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UvrY as the Cognate Response Regulator for the BarA Sensor Kinase in Escherichia coli

Abstract: BarA is a membrane-associated protein that belongs to a subclass of tripartite sensors of the two-component signal transduction system family. In this study, we report that UvrY is the cognate response regulator for BarA of Escherichia coli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
166
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(169 citation statements)
references
References 46 publications
(30 reference statements)
2
166
1
Order By: Relevance
“…Interestingly, one of the SOS promoters, uvrY, is found to have a large error (Ϸ45%). This operon has been recently found to participate in a twocomponent signaling system related to stationary-phase response (27,28), and there is evidence that it is regulated by transcription factors other than LexA (29). The relatively large 30% error of polB may hint that it also has slight, as of yet uncharacterized, additional regulation.…”
Section: Detection Of Promoters With Additional Regulationmentioning
confidence: 99%
“…Interestingly, one of the SOS promoters, uvrY, is found to have a large error (Ϸ45%). This operon has been recently found to participate in a twocomponent signaling system related to stationary-phase response (27,28), and there is evidence that it is regulated by transcription factors other than LexA (29). The relatively large 30% error of polB may hint that it also has slight, as of yet uncharacterized, additional regulation.…”
Section: Detection Of Promoters With Additional Regulationmentioning
confidence: 99%
“…The BarA/UvrY two-component system (TCS) (also referred to as GacS/GacA, VarS/VarA, ExpS/ExpA, LetS/LetA, and BarA/SirA in various species) is the primary regulator of csrB and csrC expression and is highly conserved throughout the Gammaproteobacteria (Table 1) (58,66). BarA is a membrane-bound, tripartite histidine sensor kinase that uses an unusual phosphorelay mechanism to phosphorylate its cognate response regulator, UvrY (66). BarA activity is stimulated by short-chain fatty acids (SCFAs), the potency of which is negatively correlated with the aliphatic chain length (67,68).…”
Section: Regulation Of the Csr/rsm Systemmentioning
confidence: 99%
“…We tested all thirteen HKs that are partners of other PhoB family RRs for cross activation of PhoB. We also tested the HK BarA (the partner of the NarL family RR UvrY [Pernestig et al, 2001]) because BarA has been shown elsewhere to activate the PhoB family RR OmpR [Nagasawa et al, 1992]. Our search revealed four HKs (ArcB, CreC, KdpD, and QseC) that strongly activate PhoB, two HKs (BaeS and EnvZ) that weakly activate PhoB, and eight other HKs that failed to activate PhoB [Blackman et al, 2005].…”
Section: Effect Of L-rhamnose Concentration On Activationmentioning
confidence: 99%